Competition, Conflict, and Conformity: Foreign Policy Making in the First Year of the Trump Presidency. - da Vinha, Luis (Presidential Studies Quarterly, 2019)
Donald Trump won the presidency by presenting himself to the electorate as someone who "could get things done" and by promising to upend policy making in Washington. However, the first year of the Trump presidency has been characterized as disorganized and chaotic. The president's policy detachment and his penchant for improvisation and proclivity for heeding nontraditional sources of information have contributed to this generalized perception. This article assesses Trump's management style and identifies the main dynamics involved in the administration's foreign policy–making process in its first year in office by analyzing how the advisory system functioned in the decisions to withdraw from the Paris Agreement on climate change, decertify the Joint Comprehensive Plan of Action, and recognize Jerusalem as the capital of Israel.